Implementation strategies, facilitators, and barriers to scaling up and sustaining post pregnancy family planning, a mixed-methods systematic review - Ashraf Nabhan; Rita Kabra; Nahed Allam; Eman Ibrahim; Norhan Abd-Elmonem; Nouran Wagih; Nourhan Mostafa; James Kiarie; Family Planning Research Collaborators (BMC, 2023)
Abstract Background Post pregnancy family planning includes both postpartum and post-abortion periods. Post pregnancy women remain one of the most vulnerable groups with high unmet need for family planning. This review aimed to describe and assess the quality of the evidence on implementation strategies, facilitators, and barriers to scaling up and sustaining post pregnancy family planning. Methods Electronic bibliographic databases (MEDLINE, PubMed, Scopus, the Cochrane Library, and Global Index Medicus) were searched from inception to October 2022 for primary quantitative, qualitative, and mixed method reports on scaling up post pregnancy family planning. Abstracts, titles, and full-text papers were assessed according to the inclusion criteria to select studies regardless of country, language, publication status, or methodological limitations. Data were extracted and methodological quality assessed using the Mixed Methods Appraisal Tool. The convergent integrated approach and a deductive thematic synthesis were used to identify themes and sub-themes of strategies to scale up post pregnancy family planning. The health system building blocks were used to summarize barriers and facilitators. GRADE-CERQual was used to assess our confidence in the findings. Results Twenty-nine reports (published 2005-2022) were included: 19 quantitative, 7 qualitative, and 3 mixed methods. Seven were from high-income countries, and twenty-two from LMIC settings. Sixty percent of studies had an unclear risk of bias. The included reports used either separate or bundled strategies for scaling-up post pregnancy family planning. These included strategies for healthcare infrastructure, policy and regulation, financing, human resource, and people at the point of care. Strategies that target the point of care (women and / or their partners) contributed to 89.66% (26/29) of the reports either independently or as part of a bundle. Point of care strategies increase adoption and coverage of post pregnancy contraceptive methods. Conclusion Post pregnancy family planning scaling up strategies, representing a range of styles and settings, were associated with improved post pregnancy contraceptive use. Factors that influence the success of implementing these strategies include issues related to counselling, integration in postnatal or post-abortion care, and religious and social norms. Trial registration Center for Open Science, OSF.IO/EDAKM